KARAKTERISTIK GEJALA KLINIS IBU HAMIL DENGAN INFEKSI COVID-19 DI RSUP DR. M. DJAMIL PADANG - Milano, Ryan Suheil; Defrin, Defrin; Firdawati, Firdawati; Aladin, Aladin; Russilawati, Russilawati; Revilla, Gusti (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Background: The SARS-CoV-2 virus easily spreads globally in a short period. Pregnant women are one of the vulnerable groups who can be infected with COVID-19, they have a risk of complications during pregnancy Objective: This research aims to identify the traits of expectant mothers with COVID-19 infection at Dr. M. Djamil Padang. Methods: This form of research uses retrospective descriptive approach, utilizing a comprehensive sampling and relying on secondary data sources. The research was conducted at Dr. M. Djamil Padang Hospital by taking data on pregnant women with confirmed COVID-19 infection in 2020-2021. Samples that met the inclusion and exclusion criteria were 302 cases Result: The results of this study showed the most gestational age was 3rd trimester (96.0), no clinical symptoms (58.6%), with the highest pregnancy outcomes being mature (72.5%), the highest birth weight babies being 2500-4000 grams (81,1%) and the highest maternal and infant outcomes being live mothers and babies ( 87.7%). Conclusion: This study concludes is that most pregnant women with COVID-19 infection at Dr. M. Djamil Padang in 2020-2021 with characteristics of third trimester gestational age, no clinical symptoms, mature pregnancy outcome, weight normal birth and high maternal and infant survival rates